Consumer Mindsets and In-Store Engagement Behaviors across Purchase Journeys - Oh, Hyunjoo; Youn, Chorong (International Journal of Costume and Fashion, 2024)
Shoppers move through different combinations of online and offline channels in their path-to-purchase journey. This study aims to investigate whether shopper segments by journey type exhibit distinguishable patterns of in-store behaviors due to the different mindsets they deploy during store visits. Study 1 investigates path-to-purchase journeys and identifies three segments of store visitors: offline store-only consumers, webroomers, and showroomers by sequencing all activities involved in sunglasses purchase journeys. Study 2 shows that different mindsets are present depending on the purchase journey. Study 3 demonstrates different patterns of in-store engagement behaviors among the three shopper segments in a shopping task that simulates different sequences of channel usage. The findings in studies 2 and 3 highlight the associations between mindsets and engagement behaviors among the three shopper segments. Our finding on the novel relationship between shopper segments and mindsets suggests that mindset can be a robust segmentation basis that explains both information processing and behavioral patterns in omnichannel environments. KCI Citation Count: 0